Strong-field spectra and optical near-field enhancement at aluminium needle tips - Paschen, Timo; Nauk, Constantin; Dienstbier, Philip; Hommelhoff, Peter (Journal of Physics B: Atomic, Molecular and Optical Physics, 2021)
We study the rescattering of photoemitted electrons at aluminium needle tips. For various laser intensities we measure electron energy spectra to identify telltale features of strong-field rescattering, in particular a plateau with near-constant count rate and a high-energy cutoff. This rescattering process is used to investigate the geometry-dependent enhanced optical near-field at the apex of the aluminium tip. A large near-field enhancement, extracted from the spectral data, is supported by 3D finite-difference time-domain simulations. A systematic theoretical investigation of the near-field enhancement at aluminium tips shows a strong dependence on tip opening angle and radius of curvatur
Keywords: electron sources; aluminium needle tips; strong-field physics; rescattering; optical near-fields